CHARIPINAE (HYMENOPTERA: FIGITIDAE) OF SERBIA – DISTRIBUTION AND TROPHIC INTERACTIONS (Acta Entomologica Serbica, 2019)
The distribution and trophic interactions of aphid associated Charipinae of Serbia are presented. In total, 77 different trophic associations (plant-aphid-primary parasitoid-hyperparasitoid) have been reported. Four Charipinae species are recorded for the first time from Serbia: Alloxysta citripes (Thomson, 1862), Alloxysta mullensis (Cameron, 1883), Alloxysta pusilla (Kieffer, 1902), and Alloxysta sawoniewiczi (Kierych, 1988).